Choledochal Cyst – case report - Brás, Sara Cordeiro Fernandes; Queimado, Hugo H. Dias; Tomás, Sónia Maria M.; Féria, Artur Ramon R. de la; Santos, João H. Cruz de Ascensão (Revista Portuguesa de Cirurgia, 2011)
Choledochal cysts are anatomical variations of the intra or extrahepatic biliary tree. Reported frequency rates range from 1 case per 100.000 to 1 case per 2 million with a female-to-male ratio in the range of 4:1. We report a case of a 22-year-old male, with right upper quadrant pain, carrying a gastroduodenoscopy compatible with antral gastropathy and duodenal procidence by external compression. The computed tomography (CT) scan showed a choledocal cyst with microlithiasis inside, compressing the second portion of the duodenum. The patient performed an endoscopic retrograde cholangiopancreatography (ERCP) and a cholangio-MR (MRCP), that confirmed the diagnosis. Surgery included cholecystectomy and complete excision of the cyst with sphincteroplasty. No intra or postoperative complications were observed. Keywords: Choledochal Cyst; Cyst excision; Bile ducts.